2019
DOI: 10.1111/ggi.13644
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rivastigmine transdermal therapy on low food intake in patients with Alzheimer's disease: The Attitude Towards Food Consumption in Alzheimer's Disease Patients Revive with Rivastigmine Effects study

Abstract: AimMost patients with Alzheimer's disease (AD) experience poor food intake and/or loss of appetite, which accelerates cognitive impairment. Several reports have shown that rivastigmine improves appetite in AD patients. The present study investigated the efficacy of a rivastigmine transdermal patch for the treatment of low food intake in AD patients.MethodsAD patients, recruited through the Attitude Towards Food Consumption in Alzheimer's Disease Patients Revive with Rivastigmine Effects study, were recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…25 In our study, local skin reactions were the most common (10.6%) adverse effect declared by patients and caregivers. Similar to in other studies, 26,27 gastrointestinal adverse effects were reported less frequently in our study, as patch usage was more common in these patients.…”
Section: Discussionsupporting
confidence: 91%
“…25 In our study, local skin reactions were the most common (10.6%) adverse effect declared by patients and caregivers. Similar to in other studies, 26,27 gastrointestinal adverse effects were reported less frequently in our study, as patch usage was more common in these patients.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that they also applied selective AChE inhibitor donepezil orally, but no significant differences were observed in appetite score and levels of plasma cortisol. Other authors ascribed it to the enhanced levels of plasma ghrelin, which might be a result of inhibiting BChE and the improvement of smell and taste perception through cholinergic pathways 240 . Unexpectedly, in 2018, Yoshino et al 243 observed significant decreased levels of plasma ghrelin after application of rivastigmine or donepezil, while they did not record changes of appetite or amount of food intake.…”
Section: The Role Of Bche In Obesitymentioning
confidence: 99%
“…The Neuropsychiatric Inventory disclosed 12 neuropsychiatric symptoms common in AD patients, including appetite and eating abnormalities 238 . Loss of appetite and behavioral eating disorders could be observed in more than 80% AD patients, ranging from mild to severe, which exerted a great influence on treating and nursing care 239,240 . In 2019, Ishii et al 237 pointed out the relationship between early weight loss of AD patients and the arcuate neuropeptide Y neurons, the latter of which was related to food‐intake.…”
Section: The Role Of Bche In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The drug in this form has fewer side effects. One of them is itching of the skin, as well as erythema [214][215][216]. In addition, rivastigmine reduces βA levels, has neuroprotective effects and modifies the APP processing pathway toward the non-amyloidogenic pathway.…”
Section: Drug Characteristics Disadvantagesmentioning
confidence: 99%